Efficacy of Single-Dose Albendazole for the Treatment of Soil-Transmitted Helminthic Infections among School Children in Rwanda-A Prospective Cohort Study - Joseph Kabatende; Abbie Barry; Michael Mugisha; Lazare Ntirenganya; Ulf Bergman; Emile Bienvenu; Eleni Aklillu (MDPI AG, 2023)
Mass drug administration (MDA) of single-dose albendazole to all at-risk populations as preventive chemotherapy (deworming) is recommended by WHO to halt transmission of soil-transmitted helminth (STH) in endemic countries. We assessed the effectiveness of single-dose albendazole against STH infection in the western province of Rwanda, where STH prevalence remains high despite the implementation of preventive chemotherapy for over a decade. Two weeks before the scheduled MDA, 4998 school children (5-15 years old) were screened for STH infections (Ascaris lumbricoides, Trichuris trichiura, and hookworm), and 1526 children who tested positive for at least one type of STH parasite were enrolled and received single-dose albendazole (400 mg) through MDA. A follow-up stool exam was performed at three weeks post-treatment using Kato-Katz. Efficacy was assessed by cure rate (CR), defined as the proportion of children who became egg-free, and egg reduction rates (ERRs) at three weeks post-treatment. The CR and ERR for hookworms (CR = 96.7%, ERR = 97.4%) was above, and for Ascaris lumbricoides (CR = 95.1%, ERR = 94.6%) was borderline compared with the WHO efficacy threshold (CR and ERR ≥ 95%). However, the CR and ERR for T. trichiura (CR = 17.6% ERR = 40.3%) were below the WHO threshold for efficacy (CR and ERR ≥ 50%). Having moderate-to-heavy infection intensity and coinfection with another type of STH parasites were independent risk factors for lower CR and ERR against Trichirus trichiura (p < 0.001). Single-dose albendazole used in the MDA program is efficacious for the treatment and control for hookworms and Ascaris lumbricoides infections but not effective for Trichirus trichiura. An alternative treatment regimen is urgently needed to prevent, control, and eliminate STH as a public health problem.